Price Discovery in Initial Public Offerings and the Role of the Lead Underwriter - Aggarwal, Reena; Conroy, Pat (Journal of Finance, 2000)
We examine the price discovery process of initial public offerings (IPOs) using a unique dataset. The first quote entered by the lead underwriter in the five‐minute preopening window explains a large proportion of initial returns even for hot IPOs. Significant learning and price discovery continues to take place during these five minutes with hundreds of quotes being entered. The lead underwriter observes the quoting behavior of other market makers, particularly the wholesalers, and accordingly revises his own quotes. There is a strong positive relationship between initial returns and the time of day when trading starts in an IPO.